Third‐party reporting and cross‐border tax planning - Edwards, Alexander; Hutchens, Michelle; V. Persson, Anh (Contemporary Accounting Research, 2024)
Abstract In 2018, the European Union (EU) introduced a new mandatory reporting requirement for a wide range of cross‐border tax arrangements (EU Directive 2018/822, also known as DAC6). Unlike prior corporate transparency initiatives, which put the reporting responsibility primarily on the taxpayers, this directive puts the initial reporting responsibility on the third‐party intermediaries who are involved in the reportable arrangement at any stage during the planning and execution process. We exploit the adoption of DAC6 in the EU to examine the effectiveness of third‐party reporting in curbing cross‐border tax planning by multinationals. Using a difference‐in‐differences research design, we find that affected firms reduce income shifting and report higher effective tax rates in the post‐adoption period. The reduction in income shifting is stronger for affiliates operating in countries without legal professional privilege extensions and in countries where noncompliance penalties are higher. Our results highlight the importance of strong third‐party reporting requirements in constraining cross‐border tax planning.